Analysis of Consumer Preferences on Mitsubishi Vehicles - Putra, Mario Pradana; Eddyono, Fauziah (Journal of Management and Administration Provision, 2024)
The increasingly competitive automotive industry makes consumer preferences a key to market success. This study analyzes consumer preferences for Mitsubishi vehicles, focusing on the factors of product, price, and location. The research method employed is a survey, with questionnaires distributed to 178 respondents as a sample. The collected data were analyzed using conjoint analysis to identify the factors that most influence consumer preferences.  The results indicate that the product dimension is the primary factor affecting consumer preferences, more dominant than price and dealer location. These findings imply that Mitsubishi needs to continually enhance product quality, innovate in technology, and strengthen digital services to maintain consumer loyalty and optimize marketing strategies in the automotive market.